The Metropolis and Nose Life. Sensory Memories, Odors and Emotions - Ramos, Olga (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2020)
Following Simmel's legacy, the present paper shows how ‘sensory memories’ and emotions are related to the meanings attributed to the smells of human and non-human entities in the metropolis. Based on the findings of a larger research project on urban youth in Mexico City, the article emphasizes how even though the smell is one of the most undervalued senses; it has a significant presence, not only unpleasant but also pleasant memories. In other words, these findings show how ‘sensory memory’ permits a ‘somatic work’ (Vannini et al. 2012) on the sensations and emotions that have persisted in our sensitive bodies, in which smell is not necessarily a “dissociating sense” as Simmel believed, even in the metropolis.